Assistência técnica à habitação de interesse social - Nishimura, Kawani Yuri [UNESP]; Costa, Luana Ripke da [UNESP]; Alves, Silvana Aparecida [UNESP]; Morais, Ágatha Araujo [UNESP]; Carvalho, Aline Spadotto de [UNESP]; Miguel, Antonio Carlos Signorelli [UNESP]; Pasquarelo, Bárbara Lumasini [UNESP]; Lima, Jéssica Silva [UNESP]; Oliveira, Leonardo Maggi de [UNESP]; Ribeiro, Maíra Casemiro [UNESP]; Miyamoto, Pamela Yukie [UNESP]; Battaglini, Stela Bonin [UNESP]; et al. (Universidade Estadual Paulista (Unesp), 2015)
Extension Project focused on social housing. Relevant question from the social point of view, economic and political, for it is a national problem. It proposes improvements in housing, through building projects, with individual assistance to beneficiary families.

Projeto de Extensão voltado para a Habitação de Interesse Social. Questão relevante do ponto de vista social, econômico e político, por se tratar de uma problemática nacional. Propõe melhorias nas moradias, por meio de projetos arquitetônicos, com atendimento individual às famílias beneficiadas.
Keywords: Social housing; Technical assistance; Habitação social; Assistência técnica